Emergent multimedia clusters in the Lille, Lyon and Marseille metropolitan areas - Lusso Bruno (European Regional Science Association (ERSA), 2011)
The spatial, organizational and institutional proximity plays an important part in the geography of economic development (Boschma, 2005). It is therefore important to see what kinds of networks are being developed within the multimédia sector between the different actors of the Triple Helix (Etzkowitz and Leydersdorff, 1997): firms, training and R&D facilities, and public authorities. We will take for the example three French metropolitan areas: Lille, Lyon and Marseille. The dynamism of the social networks is supported by the development of a collective governance which associates public and private actors (Maillat and Kébir, 1999). So, initiatives have launched to facilitate strategic governance of emergent regional multimédia clusters. Three forms of governance (Tremblay and Rousseau, 2005) can be distinguished: public (Pole Images Nord-Pas-de-Calais in Lille), private (Imaginove in Lyon) and public-private partnership (Pole Sud Image in Marseille). These contrasted situations result from internal conflicts in the different industries of the multimedia sector. These structures have launched several similar actions in order to the constitution of social networks. Principles are inspired by the Competitivness Clusters and Michael Porter's theories (2000). We can summarize them in the following way: - Interprofessional meetings, - Pooling of the human resources of the companies from the cluster, - Training programme for employees and executives, - Calls for collaborative projects which associate industrial and academic partners, - Support to firms willing to try out innovative business approaches, - Support programme for companies seeking to compete internationally. But, collaboration between different firms was generally low or nonexistent in spite of several regional projects (Einright, 1996). Collaborations are still very recent, rarely include a cross-media approach and hesitate to develop partnerships with research units. Similarly, the three metropolitan areas suffer from the poor adaptation of the regional training offer, which is far too rich and diverse compared to the actual capacities of the regional moving picture economy. Companies, mainly SMEs, cannot hire many people and they hesitate to embark on international missions.
Keywords: 330